A Study on Business Opportunity in Solar Panel and Solar Water Heaters Among People Staying in Ahmedabad City - Doshi, Ayushi; Yadav, Dhruv; Vidani, Dr. Jignesh (Contemporary Journal of Applied Sciences, 2024)
A project called the Suryashakti Kisan Yojana (SKY) offers a smart solution by helping farmers switch to solar-powered tubewells. This not only helps reduce water usage, but also allows them to earn money by selling the extra solar energy they generate. In Ahmedabad, another initiative is underway—a public-private partnership (PPP) to use solar energy in the city’s public transport system, making urban transport more sustainable. This study examines these issues and explores ways to encourage innovation and sustainability in Gujarat’s renewable energy sector. The findings highlight the need for stronger policies and more collaboration between businesses, government, and local communities to support green entrepreneurship. The study concludes with practical recommendations to help promote sustainable practices in Gujarat, which could also serve as a model for other developing regions looking to scale up their renewable energy efforts